Research on the evaluation system of prosthesis structure type implanted with porous structure - Zhu, Ye; Jiang, Yong; Lei, Lei; Liu, Hongchi; Guan, Tianmin (Frontiers in Transplantation, 2025)
The porous structure can effectively reduce the stress shielding effect in the process of implanting prostheses in the treatment of bone defects, but the performance of different types of porous structures directly affects the treatment effect, so it is necessary to evaluate a variety of different porous structures and select the most suitable structure type for implantation to improve the treatment effect. Based on the three-dimensional model of porous structure, this paper uses numerical analysis to evaluate the mechanical properties of porous structure and completes the primary selection of porous structure; secondly, the indexes and weights affecting the performance of porous structure are clarified, the calculation method of evaluation value is determined, and the evaluation system of implanted prosthesis with porous structure is constructed; then, through mechanical experiments and animal experiments, the machinability index and bone ingrowth index of the primary structure and commonly used clinical structure are studied; finally, according to the evaluation system, the most suitable type of porous structure for implantation is selected. The results of this study found that the tetrahedral body-centered structure [diamond structure] is the optimal structure type for the preparation of implanted prostheses with porous structures. The implantation of tetrahedral body-heart structure is of great significance for the treatment of segmental bone defects and can improve the quality of life of patients.